TECHNOLOGICAL LEARNING. PERSPECTIVE OF A UNIVERSITY COMPUTER UNIT - Martínez Garcés, Josnel (2017)
The present paper aims to describe technological learning in the Computer Unit of the Rafael Urdaneta University (Venezuela). To achieve this, a descriptive, field and non-experimental investigation was carried out using a questionnaire structured by seventeen (17) ítems as a data collection instrument. The population was made up of all the personnel working in the referred unit, which amounted to a total of three (3) key informants. The results allow to conclude that in the Computer Unit of the Rafael Urdaneta University technological learning is an element that is present in a medium-high degree as a managerial strategy in its organizational planning, also the activities of technological learning are developed to a degree Moderate-low but, consequently, technological learning if it is promoted and developed among the members that integrate the unit studied.